PROPERTIES OF ELECTRON AND NEUTRON THERAPY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The paper examines the properties of electro and neutron therapy. It is shown that after treatment with electrons, there are no visible traces on the skin at the site of previously existing tumor foci, and it is an alternative to surgical treatment methods. Neutron therapy has high biological effectiveness in the treatment of malignant neoplasms.